The mediating effect of supply chain integration on the relationship between information technology, trust and firm performance: a conceptual framework - Mohammad Bagheri, Mahdi (Penerbit UTM Press, 2014)
Supply chain Management has played a significant role in corporate efficiency and has attracted the attention of numerous academicians over the last few years. As the concept of becomes more widely accepted, supply chain integration (SCI) is gaining more attention among both practitioners and academics. The paper aims at understanding how SCI and its antecedents, impacts firm performance. For the literature review of the related academic articles for the previous studies has been taken by international journals in Logistics, Supply Chain Management and Operations Management. The study looked at some variables such as trust and information technology (IT) that might impact the SCI and finally improve firm performance. Therefore, it is crucial for managers to apply their firms IT and trust as lower-order organizational capabilities to improve SCI as a higher-order organizational capability. To aid the study, Resourced-Based View (RBV) theory has been developed as the framework for the present research. The paper also proposes the framework for future research in empirical investigation in manufacturing. This study bridges the gap by developing a framework for measuring SCI, which enables any organization to identify critical success factors for integrating their SC, measures the degree of integration qualitatively and quantitatively and suggest improvement measures.